The Influence of Marketing Mix in Increasing Sales of Bariklana Bakery Products at Kopontren Al Amien Prenduan - Mujibno Mujibno; Aidil Aminah (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the influence of the marketing mix—comprising product, price, place, and promotion—on the sales of Bariklana Bakery products at Kopontren Al-Amien Prenduan, both partially and simultaneously, as well as to identify the most dominant variables influencing sales. This study employs an associative quantitative approach using a data collection technique involving the distribution of questionnaires to 159 respondents who are consumers. The data analysis method used is multiple linear regression with the assistance of IBM SPSS software. The results indicate that, individually, the product, price, and place variables have a positive and significant effect on sales, with significance values of 0.000 < 0.05; 0.046 < 0.05; and 0.000 < 0.05, respectively, while the promotion variable does not have a significant effect with a value of 0.518 > 0.05. Simultaneously, all marketing mix variables significantly influence sales, contributing 55.7%, while the remaining 44.3% is influenced by other factors outside the research model. The product variable is the most dominant factor influencing sales, with a standardized coefficient of 0.351. These findings indicate that optimizing product quality is the key to increasing sales at Bariklana Bakery.